Strength Development and Pozzolanic Reactivity of Silica-Based Waste Glass - Norsuzailina, Sutan; Nafisa, Tamanna; Aizat, Gani; Teo, Delsye Ching Lee; Ibrahim, Yakub (2014)
This study investigates on the feasibility of using finely ground waste glass inclusion as partial cement replacement by focusing on the evidence of pozzolanic reactivity and mechanical strength properties. Two types of glass; clear and green colored, with varying particle sizes in the range of 150-75µm, 63-38 µm and <38 µm were prepared. Cement was replaced with 10%, 20%, 30% and 40% by weight glass powder with constant water to cement ratio of 0.45. The results obtained show the evidence of pozzolanic properties and higher strengh for 10% cement replacement by clear and green waste glass powder.The formation of additional C-S-H within the hydrated cement paste suggests pozzolanic reaction in the samples.